Kajian Mengenai Kesan Penganjuran Pesta Wau Antarabangsa Negeri Kelantan Terhadap Masyarakat Di Tumpat, Kelantan - Siti Fatimah, Zakaria (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study was designed to examine the effects of the International Kite Festival in Kelantan to the local community in Tumpat, Kelantan. In addition, to reviewing the impact of the International Kite Festival, the study was also conducted to know the factors fatherly involvement of local communities and management strategies undertaken by the organizers. The main focus in these study researchers studied the impacts on local communities. For more accurate survey data, quantitative and qualitative methods are used. Interviews were conducted in a way from Kelantan Tourism Information Centre and questionnaires distributed 195 sets of residents around Kampung Pantai Geting and Kampung Tujuh. The data obtained is analyzed using the SPSS program to obtain the percentage, frequency and min. Thus, overall the study found that International kite Festival in Kelantan have a positive impacts on the local community in terms of economic, social, cultural as well as environmental.